Oil Content And Physicochemical Characteristics Of Some Wild Oilseed Plants From Kivu Region Eastern Democratic Republic Of Congo - Minzangi, Kazadi; Kaaya, Archileo N.; Kansiime, Frank; Tabuti, John R.S.; Samvura, Bashwira (African Journal of Biotechnology, 2011)
Seeds were collected from Carapa grandiflora, Carapa procera, Cardiospermum halicacabum, Maesopsis eminii, Millettia dura, Myrianthus arboreus, Myrianthus holstii, Pentaclethra macrophylla, Podocarpus usambarensis, Tephrosia vogelii and Treculia africana from Kahuzi-Biega National Park and the surrounding areas in D.R. Congo. Oils were extracted using ethyl ether in Soxhlet extractor. Physicochemical characteristics were determined using the methods of the American Oil Chemists Society. The seed oil content obtained ranged from 17.2 to 64.4%; the highest was obtained from P. usambarensis and the lowest from T. vogelii. The oil specific gravity varied from 0.8050 to 0.9854; the oils melting point ranged from -12 to 32°C; the oil saponification values from 182.5 to 260.9 mg KOH/g; the oil acidity index from 1.74 to 5.31 mg KOH/g and the unsaponifiable matter from 0.54 to 2.25%. The plant seed oils content reported in this study are comparatively higher than some food crop plants such as soybean and olive. Five of these oils have oil melting range as that of edible oils. C. grandiflora, C. halicacabum, M. eminii and the two species of Myrianthus are in the range of common cooking oils by their specific gravity values. P. usambarensis seed oil with its relatively high unsaponifiable matter content can have efficacy as cosmetic.
Keywords: Physicochemical characteristics, oil content, oilseed plants, Kahuzi-Biega National Park, edible oils